2007
DOI: 10.1111/j.1574-6968.2007.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperate phages TP901-1 and ϕLC3, belonging to the P335 species, apparently use different pathways for DNA injection inLactococcus lactissubsp.cremoris3107

Abstract: Five mutants of Lactococcus lactis subsp. cremoris 3107 resistant to phage TP901-1 were obtained after treatment with ethyl methanesulfonate. Two of the mutants were also resistant to phage phiLC3. The remaining three mutants were as sensitive as 3107. Mutants E46 and E100 did not adsorb the two phages. Mutants E119, E121 and E126 adsorbed phage phiLC3 as well as 3107 but phage TP901-1 with significantly reduced efficiency. All, except E46, could be lysogenized with phage TP901-BC1034, a derivative of TP901-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The ISS1 insertion elements were shown to be located within a gene cluster that is presumed to be responsible for the biosynthesis of a CWPS. Interestingly, a similar sedimenting phenotype was observed in several (but not all) BIMs of L. lactis 3107, which had been isolated as being insensitive to phages TP901-1 and φLC3 (both of which belong to the P335 group) (25). Finally, L. lactis MG1363 mutants deficient in CWPS pellicle biosynthesis were shown to display a sedimenting phenotype and to be insensitive to the 936 group bacteriophage sk1 (20).…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…The ISS1 insertion elements were shown to be located within a gene cluster that is presumed to be responsible for the biosynthesis of a CWPS. Interestingly, a similar sedimenting phenotype was observed in several (but not all) BIMs of L. lactis 3107, which had been isolated as being insensitive to phages TP901-1 and φLC3 (both of which belong to the P335 group) (25). Finally, L. lactis MG1363 mutants deficient in CWPS pellicle biosynthesis were shown to display a sedimenting phenotype and to be insensitive to the 936 group bacteriophage sk1 (20).…”
Section: Introductionmentioning
confidence: 65%
“…It has previously been shown that certain BIMs of L. lactis 3107, which had been generated by ethyl methanesulfonate exposure, display distinctly different infection profiles with respect to phages φLC3 and TP901-1 (25). Of five TP901-1-resistant BIMs generated, two were shown to be resistant to φLC3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, that the glycosyltransferase inactivation may prevent the transfer and decoration of the required pellicle monosaccharide component to the surface thus negating the primary contact between the phage RBP and its saccharide receptor; or secondly, if primary contact is established and a membrane component is required for the translocation of the DNA across the membrane, the membrane-associated protein inactivation prevents internalisation of the phage DNA. Chemical mutagenesis of the lactococcal host strain 3107, which is sensitive to the P335 phages LC3 and TP901–1, resulted in the isolation of five genetically and phenotypically distinct mutants resistant to one or both phages [37]. This analysis revealed that the injection pathways employed by these phages of the same species are distinct.…”
Section: Structural Approaches To Understand Dairy Phage Interactimentioning
confidence: 99%